Ekonomizm nauk o zarządzaniu a przedsiębiorczość personalistyczna - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2013)
The article presents the view that the introduction of the personalistic paradigm intoentrepreneurship will enable integral economic growth and remove the causes of today’s crisis,that is economism and instrumental rationality. Personalism, which recognizes man as a consciousperson experiencing self and others, has special qualities for application. This is the most usefulapproach to philosophical and ethical analysis of the modern enterprise. In this article the focusis on a company managed according to personalistic ethics. Entrepreneurship in the personalisticapproach is the art of management, which increases the area of common good.